Correlation between IL-27p28 Genetic Polymorphisms and Risk of Allergic Rhinitis - Koohyanizadeh, Farzaneh; Falahi, Sara; Mortazavi, Seyed Hamid Reza; Salari, Farhad; Rezaiemanesh, Alireza; Karaji, Ali Gorgin (Gene expression, 2023)
Background and objectivesInterleukin 27 (IL-27) is a cytokine consisting of two subunits, p28 and EBI3, and is a key mediator in regulating the differentiation of TCD4 + cells while playing a crucial role in immune-related disorders. This study aims to elucidate the possible association between IL-27p28 single nucleotide polymorphisms (SNPs), IL-27 serum levels, and the risk of allergic rhinitis (AR).Materials and methodsBlood samples were collected from 130 patients with AR and 130 healthy individuals, and DNA and serum were separated. The relationship between IL-27p28 SNPs (rs153109 and rs181206) and the risk of AR was evaluated using the polymerase chain reaction-restriction fragment length polymorphism method. The serum levels of IL-27 in the participants were determined using enzyme-linked immunosorbent assay.ResultsOur results did not show a significant relationship between IL-27p28 SNPs (rs153109 and rs181206) and the risk of AR or serum IL-27 levels. However, our results showed a significant decrease in the serum level of IL-27 in patients with AR (342 ± 299 pg/mL) compared to healthy subjects (455 ± 274 pg/mL) (p = 0.02).ConclusionOur results suggest that IL-27p28 SNPs (rs181206 and rs153109) are not associated with susceptibility to AR, but that decreased serum IL-27 levels may be associated with the development of AR.